Evaluating optical coherence tomography (OCT) findings as potential biomarkers in central nervous system (CNS) lymphoma with or without ocular involvement - Muhammad Hassan (BMC, 2021)
Abstract Background To evaluate spectral domain optical coherence tomography (SD-OCT) findings as biomarkers in primary central nervous system lymphoma (PCNSL) with or without ocular involvement. Methods This study was a cross-sectional study and patients with a confirmed diagnosis of PCNSL with or without ocular involvement were included. Patient cohort finder tool was used to identify patients with lymphoma using ICD-10 codes (C82–C88), from January 2004 to October 2017. A total of 14,820 patients were identified. Procedure code (92134) for optical coherence tomography (OCT) was then applied to identify patients who had underdone OCT imaging at ophthalmology clinic. Clinic charts of 460 patients with lymphoma and available OCT were reviewed to identify patients with confirmed diagnosis of PCNSL and divided into two groups (Group 1: with and Group 2: without ocular involvement). OCT scans of patients in both study groups were analyzed for the presence of (1) Hyperreflective deposits in choroid, retinal pigment epithelium (RPE), outer and inner retina; (2) RPE thickening; (3) Vitreous debris; (4) Intraretinal fluid; (5) Ellipsoid zone disruption by masked graders. Chi-square was used to analyze the difference between the groups. Results Twenty-two eyes (11 patients) with PCNSL were included this study (Group 1: 6 eyes and Group 2: 16 eyes). Mean age of subjects was 65 years. Five patients (45.45%) were female. There was no statistically significant difference between the groups for the presence of hyperreflective deposits in choroid, RPE, outer and inner retina, and presence of RPE thickening, intraretinal fluid, and ellipsoid zone disruption. Vitreous debris was found more commonly in group 1 subjects (83%) than group 2 (31.25%) (p = 0.029). All subjects in both groups showed hyperreflective deposits in the RPE demonstrating RPE infiltration. However, RPE thickening was noted only in 3 patients (Group1: 1 and Group2: 2). Conclusions OCT finding of hyperreflective deposits present in eyes with lymphoma secondary to PCNSL are also observed in eyes with PCNSL without ocular disease. However, the vitreous deposits are more commonly found in eyes with ocular disease. These hyperreflective deposits can serve as biomarkers for early detection of ocular involvement by PCNSL.